Telemonitoring of older anticoagulant users during the COVID-19 pandemic - Ferreira, Lívia Cristina; Júnior, Nelson Machado do Carmo; Peixoto, Gabriel Gomes Soares Lins; Aguiar, Ana Luiza Pereira; Valle, Estevão Alves; Azevedo, Daniela Castelo; Nascimento, Mariana Martins Gonzaga do (O Mundo da Saúde, 2023)
The COVID-19 pandemic brought challenges to the monitoring of anticoagulant users, especially older adults, making telemonitoring an alternative to provide continuity of care for these patients. The present study aimed to describe the experience of telemonitoring of older anticoagulant users during the COVID-19 pandemic. This is a descriptive study concerning the telemonitoring pharmaceutical service for older adults (≥60 years old) using oral anticoagulants in a private geriatric outpatient clinic (Belo Horizonte). Older people had parameters of effectiveness and safety of anticoagulants monitored monthly by telephone (Apr-Dec/2021). Identified problems generated interventions for the patient or the multidisciplinary team. A total of 425 older adults were included in the service. Most used apixaban (189;41.9%), rivaroxaban (146;34.4%) and warfarin (47;11.1%). There was a mean age of 82.1 years, mostly female (65.2%), most at high risk of vulnerability (69%), and an incidence of 9.9% of COVID-19. There were 219 interventions related to warfarin (average of 4.6 interventions/patient); including requests for an INR test (57.5%), health guidelines (19.6%), dosage change (reduction - 10.5%; increase - 5.9%; suspension - 0.6%), or referral (5.9%). Users of other anticoagulants did not show alterations in the monitored parameters. Eleven older adults suffered falls and 10 required hospitalizations due to thromboembolic or hemorrhagic events. There was no statistically significant difference in hospitalization rates between users of warfarin or other anticoagulants (p=0.314). Monitoring older anticoagulant users is important, especially considering the high level of frailty identified and the thromboembolic and non-thromboembolic risks that COVID-19 brings. Telemonitoring was important, allowing for multiple interventions to be performed.